No more diffidence - Wan Jumani, Fauzi (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
29 June 2010. UMP Bursary staff had their five minutes of fame as they took the stage and sang their hearts out; in front of their big boss, too! It was all a stressfree moment of merriment as participants sang the familiar words of “Where’s the report?” and “No FB!” tongue-in cheek, typically heard and used at their workplace.